Caracterização petrográfica dos basaltos da Região de Tucuruí-PA - CUNHA, Rômulo Gustavo Borges da (2019)
This work is focused in the Tucuruí region and surrounding areas, placed in the northeastern Pará State. Geologically it is part of the Araguaia Belt which mostly comprises the Tucurui Group, a Neoproterozoic magmatic-sedimentary succession. It focuses on the geological and petrological characteristics of basaltic rocks of the Tucuruí Group. The main objective is to characterize the nature of magmatism and associate it to the regional context of the Araguaia Belt. The petrographic analysis involve description of both hand sample and thin section under optical microscope, also textural analysis, microstructural characterization and rock petrological classification, including scanning electron microscopy. This study is a contribution for both the regional geological context for the Araguaia Belt and more specifically to the understand of the existing successions of basaltic flows. These basalts are part of a succession of at least two main flowr interbedded with arkosic sandstones, showing a thickness of about 15 m. Petrological studies revealed three major petrographic groups including (1) massive basalts, (2) amigdaloidal basalts and (3) stroke breccias. Furthermore, by mineralogical and textural variations, it was possible to characterize subtypes. The massive basalts represent the most significant rocks associated with the Tucuruí Group. Petrographically the basalts are aphanitic, greenish gray, homogeneous, massive and after with conchoidal fracture. They show intersetal intergranular texture. The amygdaloidal basalts are dark gray, heterogeneous, massive, aphanitic, very fine grained and with conchoidal fracture. On the textural point of view these rocks show a wide textural variation types, highlighting the intergranular textures, intersetal and also amigdaloidal textures. The main subordinate mineralogy consists of plagioclase and clinopyroxene surrounded by glassy material and opaque minerals as accessories; secondarily, epidote and chlorite. The clinopyroxene fills spaces between the laths of plagioclase, characterized as intergranular texture. This texture is supposed to define the upper parts of the stroke and is characterized by having the same dimensions of the amygdales, with diameters between 2-7 mm filled by low-temperature minerals (chlorite, quartz and epidote). The clastic fragments observed in the magmatic breccias are mostly sandstones and basalts, with sizes ranging from 1 to 10 cm. They are irregular, with angular fragments of sandstone, encompassed by the basalt. The sandstone fragments are dark reddish gray, very fine grained and strongly brecciated with quartz veins of millimeter dimensions. The basaltic parts of the breccia are dark gray, aphanitic, homogeneous, massive, with intergranular texture. Their mineralogy is essentially composed of plagioclase, clinopyroxene and less opaque minerals. As a main conclusion, its pointed out that they represent a Neoproterozic tholeiitic basaltic volcanic event that was not described before in the Araguaia Belt, characterizing as a different oceanic basalt in the Araguaia Belt.